The African yam bean seed lectin affects the development of the cowpea weevil but does not affect the development of larvae of the legume pod borer - Machuka, J.; Okeola, O.; Chrispeels, M. (Elsevier, 2000)
Artificial feeding assays were used to study the effect of purified galactose-specific lectins from African yam beans (Sphenostylis stenocarpa) on development of larvae of the cowpea weevil, Callosobruchus maculatus (Coleoptera: Bruchidae) and the legume pod-borer, Maruca vitrata (Lepidoptera: Pyralidae). Inhibition of development of C. maculatus was observed when larvae were fed on artificial cowpea seeds containing 0.2%, 2.0% and 5.0% (wt/wt) of dietary lectin. Larval mortality was between 30% and 88%, while delays in total developmental time ranged between 7 and 13 days. The lectin had no effect on development of larvae of M. vitrata, when tested through topical artificial diet incorporation assays, except at the extremely high dose of 35% dietary level.